Review: Presidential Job Approval. Issue 1 (5th July 2021) - Newport, Frank; Saad, Lydia
Abstract: Presidential job approval is arguably the most important time series in US polling history and likely the most well-understood public opinion measure in popular American culture. This article examines the history of the measure going back to its origination during the Roosevelt administration, the value of presidential job approval in assessing the timeline of US history, the life cycle of presidential approval within administrations, and the relationship between presidential approval and incumbent reelection. The evidence indicates increasingly rigid partisan politicization in presidential-approval ratings, suggesting less variation in approval in the future, fewer so-called rally events, and the possibility that job approval may become more of a measure of party loyalty than actual presidential performance assessment.